Advanced Progress of Optical Wireless Technologies for Power Industry: An Overview - Jupeng Ding; Wenwen Liu; Chih-Lin I; Hui Zhang; Hongye Mei (Applied Sciences, 2020)
Optical wireless communications have attracted widespread attention in the traditional power industry because of the advantages of large spectrum resources, strong confidentiality, and freedom from traditional electromagnetic interference. This paper mainly summarizes the major classification and frontier development of power industry optical wireless technologies, including the indoor and outdoor channel characteristics of power industry optical wireless communication system, modulation scheme, the performance of hybrid power line, and indoor wireless optical communications system. Furthermore, this article compares domestic and foreign experiments, analyzes parameters for instance transmission rate, and reviews different application scenarios such as power wireless optical positioning and monitoring. In addition, in view of the shortcomings of traditional power technology, optical wireless power transfer technology is proposed and combined with unmanned aerial vehicles to achieve remote communication. At last, the main challenges and possible solutions faced by power industry wireless optical technologies are proposed.